Arte e esfera pública: hibridismos e processos criativos em performance, dança-teatro e videodança - Gianordoli, Julia Calmon Bolsanelo (2019)
This research was guided by the need to know the history, artists and processes that involve the public and political dimension of artists who develop their works built in the intersection of plastic arts and dance, in particular seeking to reach the capi